Analisis Pengaruh Produk, Harga, Promosi dan Lokasi Terhadap Keputusan Pembelian Pada UD. Aneka Karya Glass Di Surakarta - Syahrial, Yusroni Akhmad; , Nur Ahmad, S.E., M.Si (2015)
The aim in this study was to analyze the effect of the product purchase decision in Various Glass Works Surakarta. Analyzed the price of the Purchase Decision Aneka Glass Works Surakarta. Analyzing the Promotion of the Purchase Decision Aneka Glass Works Surakarta. Analyzing the location of the Purchasing Decisions in Various Glass Works. The population in this study are all consumers who buy at Aneka Glass Works Surakarta, while the samples used by 50 respondents. The sampling technique used is the Convenience Sampling. The analysis tool used is normality test, multicollinearity, heteroscedasticity test, test the coefficient of determination (R2), F test (Test Accuracy Model) and t test (Test of Hypothesis). Based on the results of data analysis known product variable positive and significant influence on purchasing decisions, meaning that the higher the consumer's perception of the product, the more strongly encourage consumers to make purchasing decisions. Variable rates positive and significant impact on purchasing decisions, meaning that the higher consumer perceptions of price, the more powerful push consumers to make purchasing decisions. No promotion variables and no significant positive effect on purchasing decisions, meaning that the lower the consumers' perception of the promotion, it will be increasingly weaker encourage consumers to make purchasing decisions. Variable locations positive and significant impact on purchasing decisions, meaning that the higher the consumer's perception of the location, the more strongly encourage consumers to make purchasing decisions. Rated R square (R2) obtained at 0.669. This means that the variation of the variable changes in the purchasing decision can be explained by the variable product (X1), price (X2), promotion (X3) and location (X4) amounted to 66.9%. While the remaining 33.1% is explained or influenced by external factors other than the independent variables in the regression. Keywords: Product, Price, Promotion, Location and Purchase Decision.